2023
DOI: 10.1002/mgea.4
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations of nucleation and growth of CaCO3 with the influence of inhibitors: A review

Yue Li,
Hongbo Zeng,
Hao Zhang

Abstract: Calcium carbonate (CaCO3) is a crucial mineral with great scientific relevance in biomineralization and geoscience. However, excessive precipitation of CaCO3 is posing a threat to industrial production and the aquatic environment. The utilization of chemical inhibitors is typically considered an economical and successful route for addressing the scaling issues, while the underlying mechanism is still debated and needs to be further investigated. In this context, a deep understanding of the crystallization proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 286 publications
0
3
0
Order By: Relevance
“…While electrostatics play a role in drawing cations near the macromolecule, the intensity and longevity of the interaction are typically stabilized by entropic effects [28][29][30]. CaCO 3 (and other Ca mineral) ion pair formation is also water/entropy motivated [31][32][33]. Therefore, ion and macromolecule hydration must both be accounted for when considering binding mechanisms and polymer design.…”
Section: Ion-binding At the Macromolecule-solution Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…While electrostatics play a role in drawing cations near the macromolecule, the intensity and longevity of the interaction are typically stabilized by entropic effects [28][29][30]. CaCO 3 (and other Ca mineral) ion pair formation is also water/entropy motivated [31][32][33]. Therefore, ion and macromolecule hydration must both be accounted for when considering binding mechanisms and polymer design.…”
Section: Ion-binding At the Macromolecule-solution Interfacementioning
confidence: 99%
“…Error estimation and limited experimental data also contribute. The issue becomes impressively complex as other ions and interfaces are introduced to the system [33,[105][106][107]. Further, scaling up from the atomic level to bulk solution expounds uncertainty and error.…”
Section: Computationmentioning
confidence: 99%
“…9,17 Under seawater conditions carbonate ion is known to form ion pairs 18 most notably with Mg, Ca and Na cations, 17,19 resulting in merely 8% of the total carbonate existing as free ions. 17 It is evident that the ionic composition of seawater plays an integral role in the calcium carbonate chemistry not only at the heterogeneous calcite–water interface 20,21 but also chemically in the solution phase. Note that more recent studies observed the recession/growth of pristine surface and kink sites of calcite surfaces using atomic force microscopes allows mechanistic insights into particle dissolution/crystallisation at the nanoscale level with or without calcite dissolution/growth inhibitors to be inferred.…”
Section: Introductionmentioning
confidence: 99%